2021
DOI: 10.1038/s41598-021-84411-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics shows the Australian dingo has a unique plasma profile

Abstract: Dingoes occupy a wide range of the Australian mainland and play a crucial role as an apex predator with a generalist omnivorous feeding behaviour. Dingoes are ecologically, phenotypically and behaviourally distinct from modern breed dogs and have not undergone artificial selection since their arrival in Australia. In contrast, humans have selected breed dogs for novel and desirable traits. First, we examine whether the distinct evolutionary histories of dingoes and domestic dogs has lead to differences in plas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The dingo genome’s assembly, annotation, and comparative analyses show that it has diverged from domestic dog breeds. This divergence has previously been shown to influence the plasma metabolome ( 26 ), gastric capacity, and the digestion of proteins ( 35 , 36 ), behaviors ( 1 ), and cranial morphology ( 37 ). In the next section, we test whether these differences influence the functions of epigenetic signaling, the circulatory metabolome, and the gut microbiome of dingoes and GSDs.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The dingo genome’s assembly, annotation, and comparative analyses show that it has diverged from domestic dog breeds. This divergence has previously been shown to influence the plasma metabolome ( 26 ), gastric capacity, and the digestion of proteins ( 35 , 36 ), behaviors ( 1 ), and cranial morphology ( 37 ). In the next section, we test whether these differences influence the functions of epigenetic signaling, the circulatory metabolome, and the gut microbiome of dingoes and GSDs.…”
Section: Resultsmentioning
confidence: 97%
“…Yadav et al . ( 26 ) showed that UDPgal levels were significantly lower in GSD than in dingoes. This is consistent with the observations that the GSD GAL3ST1 promoter has increased methylation and lower transcript abundance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations